G354 The ongoing rapid and significant rise of incident paediatric-onset inflammatory bowel disease in scotland. (27th April 2015) - Jagger, FA; Cameron, FL; Henderson, P; Rogers, P; McGrogan, P; Loganathan, S; Russell, RK; Hansen, R; Wilson, DC
Abstract : Background: The worldwide incidence of paediatric-onset inflammatory bowel disease (PIBD) is rising, with Scotland having the highest rate in the UK. Scottish PIBD data over the last 40 years has shown a consistent increase, including a 76% rise over 13 years around the millennium (Henderson P et al . IBD 2012;18:999–1005). Aims: The aim of this study was to calculate current PIBD incidence rates in Scotland and to determine if the temporal trend of significant increase has been maintained. Methods: Historical data from 2003–2008 (cohort 1) was compared to prospective, nationwide data of all incident cases diagnosed in paediatric services (under 16 years of age) from 2009–2013 (cohort 2). Age-sex adjusted incidence rates were calculated using population data from the General Registrar's Office for Scotland. Cases were classified as Crohn's disease (CD), ulcerative colitis (UC) or inflammatory bowel disease unclassified (IBDU) and diagnosed according to the Porto criteria. Statistical analysis was performed using Poisson regression. Results: A total of 436 patients were diagnosed with PIBD over six years in cohort 1 (265 CD, 115 UC, 56 IBDU) compared to 478 children over five years in cohort 2 (286 CD, 126 UC, 66 IBDU). Median age at diagnosis in cohort 2 (60% males) was 12.3 years, similar to cohort 1 (58% males) at 11.9 years. The adjusted incidence rate increased from 7.8/100, 000/year (95% CI 7.1–8.6) in cohort 1 (2003–2008) to 10.4/100, 000/year (95% CI 9.6–11.5) in cohort 2 (2009–2013) (p < 0.001). This significant increase was also seen individually for CD (4.7/100, 000/year [95% CI 4.2–5.4] compared to 6.3/100, 000/year [95% CI 5.6–7.0] [p < 0.0001]) and UC (2.1/100, 000/year [95% CI 1.7–2.5] compared to 2.7/100, 000/year [95% CI 2.3–3.3] [p = 0.009]). There was a non-significant increase in IBDU from 1.0/100, 000/year (95% CI 0.7, 1.3) in cohort 1 to 1.4/100, 000/year (95% CI 1.1, 1.8) in cohort 2 (p = 0.07). Conclusion: There continues to be an ongoing rise in incident PIBD (and both CD and UC) in 2009–13 in this national, population-based study compared to recent historical data, with a further significant rise of 33%. The reasons behind this continued increase remain unclear and further research is needed to elucidate potential factors in aetiopathogenesis.